Association of a MiR-499 SNP and risk of congenital heart disease in a Chinese population - Guo, Rui; Feng, Zhiyu; Yang, Yanliang; Xu, Huihui; Zhang, Jian; Guo, Kai; Bi, Yanwen (Cellular and Molecular Biology, 2018)
MicroRNAs (miRNAs) play an important role in heart development. Single nucleotide polymorphisms (SNPs) in miRNAs have been shown to associate with congenital heart disease (CHD). Methionine synthase (MTR), a key enzyme of folate metabolism, is involved in the early embryonic development. In this study, we aimed to test whether MTR is a direct target of miR-499, and to estimate the associations between miR-499 polymorphisms and the risk of CHD in Chinese population. Gene polymorphisms were analyzed in 1615 subjects including 792 healthy controls and 823 CHD patients. The miR-499 SNP were genotyped and the associations between the SNP frequencies and CHD were assessed by computing odds ratios (ORs) and 95% confidence intervals (95% CIs), as well as by applying Chi-square tests. Dual reporter assay was carried out to test whether MTR is a direct target gene of miR-499. The miR-499 rs374644 AG genotype was not associated with the CHD risk (AG vs. AA. OR=1.27, 95%CI=0.85-1.81, p=0.20). The GG genotype was associated with a significantly increased CHD risk (GG vs. AA. OR=5.33, 95%CI=1.80-15.83, p=0.001). The AG/GG variants were associated with a significantly increased CHD risk, compared with the AA genotype (OR=1.56, 95%CI=1.16-2.10, p=0.003). MiR-499 mimics inhibits the expression of MTR. MiR-499 directly targeted on MTR. Thus, our study suggested that miR-499 directly targets on MTR and the polymorphisms of rs3746444 may be associated with CHD risk in Chinese individuals.